A remark on the set of arbitrage‐free prices in a multi‐period model. (8th April 2013) - Cornet, Bernard; Ranjan, Abhishek
Abstract: We study the convexity property of the set Q ℱ of arbitrage‐free prices of a multi‐period financial structure ℱ . The set of arbitrage‐free prices is shown to be a convex cone under conditions on the financial structure ℱ that hold in particular for short‐lived assets. Furthermore, we provide examples of equivalent financial structures ℱ and ℱ ′ such that Q ℱ is a convex cone, but Q ℱ ′ is neither convex nor a cone.